Low temperature, solution processed metal oxide buffer layers fulfilling large area production requirements - Stubhan, Tobias; Litzov, Ivan; Li, Ning; Wang, Hao; Krantz, Johannes; Machui, Florian; Steidl, M.; Oh, H.; Matt, Gebhard; Brabec, Christoph (Proceedings of SPIE, 2012)
This paper is a review of our previous work on the field of low temperature, solution processed metal oxide buffer layers published in various journals. Our work focuses on zinc oxide (ZnO) and aluminum-doped zinc oxide (AZO) as n-type and molybdenum oxide (MoO3) as p-type solution processed buffer layer. In addition to that, we investigate the surface modification of AZO using phosphonic acid-anchored aliphatic and fullerene self assembled monolayers (SAMs
Keywords: Aluminum-doped zinc oxide; Low temperatures; Metal oxides; P-type; Phosphonic; Production requirements; Solution-processed; Zinc oxide (ZnO) Engineering controlled terms: Aluminum; Metallic compounds; Molybdenum oxide; Optical waveguides; Organic acids; Self assembled monolayers; Temperature; Zinc oxide Engineering main heading: Buffer layers